1979
DOI: 10.1007/bf02533464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets high in saturated fat and cholesterol on the lipid composition of canine platelets

Abstract: The phospholipid composition of platelets from dogs on various experimental diets was determined. Thyroidectomized foxhounds were fed a control diet or the control diet supplemented with (1) beef tallow, (2) beef tallow and cholesterol, or (3) beef tallow, cholesterol, and safflower oil for 23 weeks prior to isolation of platelets. Platelets from animals fed the control diet contained 36.7% phosphatidylcholine (PC), 22.8% phosphatidylethanolamine (PE), 18.4% sphingomyelin (Sph), 11.8% phosphatidylserine (PS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Cholesteryl ester concentration in platelets from hypercholesterolemic rabbits (70 #g/mg protein) was much higher than control (8 #g/mg protein). A previous report suggested that the decreased arachidonic acid in platelets from canines fed a cholesterol diet was the result of use of arachidonic acid for cholesteryl ester synthesis (28). In our experiments, cholesterol esterification was promoted and cholesteryl esters were increased in platelets.…”
Section: Cholesteryl Esterase Activitysupporting
confidence: 61%
“…Cholesteryl ester concentration in platelets from hypercholesterolemic rabbits (70 #g/mg protein) was much higher than control (8 #g/mg protein). A previous report suggested that the decreased arachidonic acid in platelets from canines fed a cholesterol diet was the result of use of arachidonic acid for cholesteryl ester synthesis (28). In our experiments, cholesterol esterification was promoted and cholesteryl esters were increased in platelets.…”
Section: Cholesteryl Esterase Activitysupporting
confidence: 61%
“…When exposed to the outer platelet membrane, arachidonic acid is available to be used as a substrate for thromboxane synthesis leading to platelet aggregation (Pitas et al, 1979;Boberg et al, 1985). In our study, we found a positive correlation between arachidonic acid and FV activity.…”
supporting
confidence: 47%
“…In particular, the PS content of GSD platelets (11.1%) was nearly identical to that of control dogs (10.7%) and to a previously reported value of canine platelet PS content (11.8%). 43 …”
Section: Platelet Phospholipid Compositionmentioning
confidence: 99%